If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -110 + 2x = 142 + 11x Solving -110 + 2x = 142 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -110 + 2x + -11x = 142 + 11x + -11x Combine like terms: 2x + -11x = -9x -110 + -9x = 142 + 11x + -11x Combine like terms: 11x + -11x = 0 -110 + -9x = 142 + 0 -110 + -9x = 142 Add '110' to each side of the equation. -110 + 110 + -9x = 142 + 110 Combine like terms: -110 + 110 = 0 0 + -9x = 142 + 110 -9x = 142 + 110 Combine like terms: 142 + 110 = 252 -9x = 252 Divide each side by '-9'. x = -28 Simplifying x = -28
| 2x-4+7=3x-5 | | 2x-19+1+2x=90 | | x+2.3=6.7 | | -3x-16=-43 | | (3x-4)(2x-5)=0 | | -13+37=8x | | 12+5x=20+3x | | -12x-9=15-10x | | (x+3)(x-7)=9 | | 2x-4+8=3x-5 | | 5+x+x+6=41 | | 1.9v=3.04 | | 5x-12=8+6x-x | | O=4-3x | | 144=30y | | -161-7x=99+3x | | 8x-y-6z=35 | | (x^2-9)^1/2-x=-3 | | 12x-(6+5x)= | | 6d+3+3(4d-1)=-2(-4d+15) | | 1.9=3.04 | | x/-8=6 | | 5[2x+8]=-90 | | 7x-3=2x-11 | | 1/2x^-x-8 | | -3x^2+12x-1=0 | | 4.9-1.97x=5-2.06x | | w^2-4w+24=0 | | 15-(4x+3)=-4x+12 | | 4+2x^3=58 | | 3[x-2]=9 | | s/3-4=4 |